Rancang Bangun Sistem Informasi Rukun Tetangga Berbasis Android Dengan Menggunakan Metode Rapid Application Development - Rahmadi .; Sabar .; Mumtaz Muttakin; Asep Udin (Jurnal ICT: Information Communication & Technology, 2022)
The Neighborhood Association are community organizations that are recognized and fostered by the government to maintain and preserve the values of Indonesian people's life based on mutual cooperation and kindship. The Neighborhood Association has the duty to serve the residents in managing the administration. The problem faced by the caretaker of the neighborhood association is that data management is done manually. To simplify the task of the neighborhood association, a web- and mobile-based data management application was created. By using the Rapid Application Development method, the author can develop the system in a shorter time than other methods because the Rapid Application Development Method uses the Prototype model. The neighborhood unit information system can receive information made by the management without having to visit every resident's house and payment of contributions can be made by means of inter-bank transfers or via e-wallet application.